Improved serodiagnosis of Trypanosoma vivax infections in cattle reveals high infection rates in the livestock regions of Argentina. - Iván Alejandro Bontempi; Diego Gustavo Arias; Graciela Verónica Castro; Luz María Peverengo; Genaro Francisco Díaz; Martín Allassia; Gonzalo Greif; Iván Marcipar (Public Library of Science (PLoS), 2024)
Bovine trypanosomosis, caused by Trypanosoma vivax, currently affects cattle and has a significant economic impact in sub-Saharan Africa and South America. The development of new diagnostic antigens is essential to improve and refine existing methods. Our study evaluated the efficacy of two recombinant antigens in detecting specific antibodies in cattle. These antigens are derivatives of an invariant surface glycoprotein (ISG) from T. vivax. A fraction of a previously described antigen (TvY486_0045500), designated TvISGAf, from an African strain was evaluated, and a new ISG antigen from an American isolate, TvISGAm, was identified. The two antigens were expressed as fusion proteins in Escherichia coli: TvISGAf was fused to the MBP-His-tag, and TvISGAm was obtained as a His-tag fused protein. An ELISA evaluation was conducted using these antigens on 149 positive and 63 negative bovine samples. The diagnostic performance was enhanced by the use of a combination of both antigens (referred to as TvISG-based ELISA), achieving a sensitivity of 89.6% and specificity of 93.8%. Following the validation of the TvISG-based ELISA, the seroprevalence of T. vivax infection in 892 field samples from cattle in the central region of Argentina was determined. The mean seroprevalence of T. vivax was 53%, with variation ranging from 21% to 69% among the six departments studied. These results support the use of the TvISG ELISA as a valuable serological tool for the detection and monitoring of T. vivax infection in cattle. Furthermore, we report for the first time the seroprevalence of T. vivax in Argentina, which highlights the widespread endemic nature of the disease in the region. In order to effectively manage the increasing spread of T. vivax in the vast livestock production areas of South America, it is essential to implement consistent surveillance programs and to adopt preventive strategies.